Response of T. Aman and Boro Rice to Residue Retention Under Strip Tillage (Bangladesh Agronomy Journal, 2016)
An on-farm research was conducted at Gouripur upazila under Mymensingh district of Bangladesh during aman and boro season in 2013-14 to evaluate the performance of unpuddled rice cultivation. The rice var. Hybrid Krishan2 in aman and BRRI dhan28 in boro season were transplanted by two tillage practices viz., conventional tillage (CT) and strip tillage (ST) and two levels of crop residue i.e, no residue (R0) and 50% residue (R50). The experiment was designed in a randomized complete block design with four replications. ST yielded higher grains in aman season (5.67 t ha-1) and also in boro season (4.70 t ha-1) which were 9 and 13% higher compared to CT. Higher grain yield in ST leading to 26% higher BCR in aman and 23% higher in boro compared to CT. Retention of 50% residue increased by 5% yield in aman and by 4% yield in boro compared to no residue which contributed to 9% higher BCR in both aman and boro. ST combine with 50% residue retention yielded the highest grain yield in both of aman (5.97 t ha-1) and boro season (4.81t ha-1) which attributed to obtain the highest BCR in aman (3.08) and boro (2.78).Bangladesh Agron. J. 2015, 18(2): 39-44